2019
DOI: 10.1002/ajpa.23801
|View full text |Cite|
|
Sign up to set email alerts
|

Revisiting traumatic injury risk and agricultural intensification: Postcranial fracture frequency at Cerro Oreja in the Moche Valley of north coastal Peru

Abstract: Objectives: In Lambert and Welker (2017) we explored the association between subsistence economy and postcranial fracture prevalence, finding that low-intensity agriculturalists exhibited significantly lower fracture rates than foragers or high-intensity agriculturalists. Here, we explore the impacts of sampling strategy on fracture rates in a sample of high-intensity agriculturalists from the Moche Valley, Peru, and further test the hypothesis that postcranial fracture risks are higher for intensive agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A global comparative analysis has shown that high‐intensity agriculturalists employing cultivation techniques designed to increase harvest, low‐intensity agriculturalists practicing only minimal landscape modification, and hunter‐foragers have predictable differences in traumatic injury risk regardless of geographic locality (Lambert & Welker, 2017, 2019). High‐intensity agriculturalists and hunter‐gatherers exhibit significantly higher rates of long bone fractures in contrast to low‐intensity agriculturalists (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…A global comparative analysis has shown that high‐intensity agriculturalists employing cultivation techniques designed to increase harvest, low‐intensity agriculturalists practicing only minimal landscape modification, and hunter‐foragers have predictable differences in traumatic injury risk regardless of geographic locality (Lambert & Welker, 2017, 2019). High‐intensity agriculturalists and hunter‐gatherers exhibit significantly higher rates of long bone fractures in contrast to low‐intensity agriculturalists (ibid).…”
Section: Introductionmentioning
confidence: 99%